Nonalcoholic fatty liver disease diagnosed by transient elastography with controlled attenuation parameter in unselected HIV monoinfected patients. (13th November 2016) - Vuille-Lessard, Élise; Lebouché, Bertrand; Lennox, Lynda; Routy, Jean-Pierre; Costiniuk, Cecilia T.; Pexos, Costa; Giannakis, Andreas; Szabo, Jason; Klein, Marina B.; Sebastiani, Giada
Abstract : Objective: Nonalcoholic fatty liver disease (NAFLD) is the most common liver disease in Western countries. HIV-infected persons without viral hepatitis are at increased risk of NAFLD. Nevertheless, data on NAFLD in HIV monoinfection are scarce. Design/methods: We prospectively investigated prevalence and predictors of NAFLD and liver fibrosis by transient elastography and associated controlled attenuation parameter (CAP) in unselected HIV-infected adults without significant alcohol intake or viral hepatitis coinfection. NAFLD was defined as CAP at least 238 dB/m. Significant liver fibrosis and cirrhosis were defined as transient elastography measurement at least 7.1 and 13 kPa, respectively. Predictors of NAFLD and significant liver fibrosis were determined using logistic regression analysis. Results: A total of 300 consecutive patients (mean age 50 years, 77% men; mean CD4 + cell count 570 cells/μl, 90% on antiretrovirals) were included as a part of a routine screening program. Transient elastography with CAP identified NAFLD and significant liver fibrosis in 48 and 15% of cases, respectively. NAFLD was independently associated with BMI more than 25 kg/m 2 [adjusted odds ratio (aOR) 4.86, 95% confidence interval (CI) 2.55–9.26] and elevated alanine aminotransferase (ALT) (aOR 3.17, 95% CI 1.43–7.03). Independent predictors of significant liver fibrosis were diabetes (aOR 5.84, 95% CI 1.91–17.85), elevated ALT (aOR 3.30, 95% CI 1.27–8.59) and current use of protease inhibitors (aOR 3.96, 95% CI 1.64–9.54). Conclusion: NAFLD and significant liver fibrosis diagnosed by transient elastography with CAP are major comorbidities in unselected HIV monoinfected persons on antiretroviral therapy, particularly if metabolic conditions and elevated ALT coexist. Noninvasive screening for NAFLD should be implemented in this population to establish early interventions and prevent complications.